Legal Accountability for Verbal Sexual Harassment Perpetrators on Dating Apps - Rufinus Hotmaulana Hutauruk; Abdurrakhman Alhakim; Salma Rayani Rosniar (Universitas of Muhammadiyah Makassar, 2023)
Numerous incidents of verbal sexual harassment are frequently encountered, and in conjunction with the rapid advancements in technology, such actions have become increasingly prevalent. The proliferation of information technology has made information more accessible, exemplified by the emergence of dating applications, demonstrating the speed of the digital world. The current impact of technological swiftness exhibits both positive and negative consequences. This study seeks to examine Indonesian legal regulations pertaining to verbal sexual harassment via dating applications. This research employs a normative research approach, characterized as a legal library research method. The findings of this study indicate that the investigation primarily relies on secondary legal materials, encompassing both primary and secondary legal sources. Up to this point, the legal protection provided by Indonesia to victims of verbal sexual harassment through dating apps predominantly relies on the penal sanctions outlined in the Penal Code, specifically under Chapter XIV addressing Crimes Against Morality, as well as several other relevant legislations governing this matter.